FACTORSAFFECTINGSTUDENTS’ENTREPRENEURIAL INTEREST IN INFORMATICSANDBUSINESSINSTITUTE DARMAJAYA - Ardianingsih, Binti; Winata, Andri (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The objective of this research was determining the factors affecting the students’ entrepreneurial interest in Informatics and Business Institute (IBI) Darmajaya. The type of this research was the quantitative descriptive research. The number of population of this research was 3,881 students who took the Technopreneurship course in 2014 –2017.   The number of sample of this research was 98 students determined by Slovin formula with 10% of standard error. The sampling technique used in this research was the purposive random sampling. The research instrument used in this research was a questionnaire used to measure the variables of this research (Capital, Innovation, creativity, Income, Education, Feelings of Pleasure, Environment, and Technological Environment). Data analysis techniques used in this research was Multiple Linear Regression Analysis. The result of this research was that the students’ entrepreneurial interest was affected by Income, Environment, and Technological Environment; while, Capital, Creativity, Innovation,   Education, and Feelings of Pleasure were not significant. Keywords : Entrepreneurial Interest,FactorsAffecting, and IIB Darmajaya